Eeffect of Solvent Fungi, Application Period And Phosphate Fertilizer In Increasing Absorption And Availlablity P of Potato In Eruption Impact of Andisol - Dilly Pratikto Suandi (Universitas Sumatera Utara, 2016)
Andisol consist of total P in a huge amount however it is in unavailable form for plant to uptake. One of the treatment to increase phosphate available on soil by using fungi. The objective of research was to determine the effect from penicillium inoculum, the time of inoculum application and SP-36 fertilizer dosage in the growth of potato and soil P availability. The experiment design used was randomized block design with three factors and three replications. The first factor was the penicillium inoculum with three stages (10, 20 and 30 mL), the second factor was the application period with two stages (1 and 2 week after plant growth) and the third factor was SP-36 fertilizer dosage with three dosages (50, 75 and 100%) from dosage used by local farmer. The parameters were microorganism population, pH, total P, P available, shoot dry weight and P uptake by plant. The result showed that penicillium inoculum was able to increase total P, P available and shoot dry weight of potato. The interaction between 30 mL of penicillium inoculum, time of application inoculum at 2 week after plant growth and 50% dosage of phosphate produce the highest potatoes shoot dry weight.